The Importance of Entrepreneurial Orientation's Dimensions in Influencing the Organizational Performance of Food and Beverage SMEs - Abdulsamad, AKRAM; Ali, Noor Azman; Mahomed, Anuar Shah Bali; Hashim, Haslinda; Jandab, Abdulwahab; Al-Sharif, Abdulrahman M. (Advances in Social Sciences Research Journal, 2020)
The study is attempted to examine and analyze the important influence of entrepreneurial orientation components - risk-taking, innovativeness, and proactiveness- on the organizational performance of Yemeni Small and Medium Enterprises within the food and beverage industry. The model of study is tested on 459 owners/Managers of SMEs by employing the analysis of Partial Least squares structural equation modeling (PLS-SEM), as well as Importance-Performance Map Analysis (IPMA). After utilizing the cross-sectional approach, the results illustrated that the innovativeness and risk-taking have a significant and positive impact on organizational performance, but their effect was less than proactiveness. Moreover, the analysis of importance-performance pointed out that proactiveness more important than innovativeness and risk-taking in determining organizational performance. The model of study expounded 34% of the whole variance in SME's performance. Moreover, it provided the implications of practical and theoretical.